2006
DOI: 10.3354/meps306041
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic sufficiency in distinguishing natural spatial patterns on an estuarine shoreline

Abstract: Studies of marine benthic communities have shown that pollution impacts can often be detected without identifying taxa to the species level, thus saving considerable time and cost. We tested whether differences among unpolluted intertidal communities along weak estuarine physical gradients could similarly be detected with various species aggregates. We used a spatially hierarchical sampling design to study species-rich, low-shore communities from pebble-sand beaches in Puget Sound, Washington. Previous researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 23 publications
5
39
1
Order By: Relevance
“…We recognize that this level of resolution can only detect changes in macrofauna community composition that occur at a high taxonomic level (i.e., order and above). Other researchers have shown that stressor impacts may become less discernible as we shift the analysis from low (i.e., species, genus, and family) to higher taxonomic levels; however, similar trends have been detected with various taxonomic levels (e.g., Warwick 1988, Olsgard and Somerfield 2000, Dethier and Schoch 2006. Thus, our study may be missing some burial impacts on community composition that occur at low taxonomic levels.…”
Section: Macrofaunal Measurementscontrasting
confidence: 38%
“…We recognize that this level of resolution can only detect changes in macrofauna community composition that occur at a high taxonomic level (i.e., order and above). Other researchers have shown that stressor impacts may become less discernible as we shift the analysis from low (i.e., species, genus, and family) to higher taxonomic levels; however, similar trends have been detected with various taxonomic levels (e.g., Warwick 1988, Olsgard and Somerfield 2000, Dethier and Schoch 2006. Thus, our study may be missing some burial impacts on community composition that occur at low taxonomic levels.…”
Section: Macrofaunal Measurementscontrasting
confidence: 38%
“…Analysis of broader taxa is therefore often used to identify spatial patterns because individual species are often very patchy and their counts dominated by many zeros. Dethier & Schoch (2006) showed strong correlations between patterns of species and families along an estuarine gradient. Similarly, Olsgard et al (2003) showed that distributions of polychaete species in sediments are well correlated with distributions at the scale of family.…”
Section: Introductionmentioning
confidence: 94%
“…spatial replication of samples within an area, and to some extent, this constrained our ability to identify every organism to the species level. However, taxonomic identification at the genus, and even family or complex, level can be sufficient for distinguishing natural spatial patterns (Dethier and Schoch 2006). Our samples (transects) consisted of the mean values from 10 sample units (quadrats).…”
Section: Methodsmentioning
confidence: 99%